Ambientes favoráveis à produção das plosivas no desvio fonológico - Berticelli, Aline (2012)
Purpose: To verify which linguistic and extralinguistic variables influence the correct production of plosive phonemes in children with atypical phonological development. Methods: Speech data from 45 children with atypical phonological development were used. The data are part of a data basis in which 17 girl and 28 boys were selected. The subjects were between four and eight years old. The considered linguistic variables were word position, tonicity, number of syllables, preceding and following context, and repair strategies. The considered extralinguistic variables were sex, degree of phonological disorder, and age. The statistic analysis was carried out through the statistical program Varbrul. Results: The correct production of /p/ was supported by moderate-severe and mild-moderate disorder groups, post-tonic syllable, following context with //, female sex. The plosive acquisition occurred with 5:6; the correct production of /b/ was supported by the group mild-moderate, preceding context /o/, following context /i/, male sex, and the variant no repair strategy prevailed, and the segment was not acquired until 7:5; the production of /t/ was supported by the mild disorder group, words with one syllable, preceding context //, following context /ãn/, male sex, the variant no repair strategy prevailed and the phoneme was acquired with 5:6; for the phoneme /d/, the correct production was supported by the male sex, words with four syllables or more, preceding context //, following context /en/, mild disorder group, no repair strategy was prevalent and the segment was not acquired until 8:0; for the phoneme /k/, the correct production was favorable in post-tonic syllables, preceding context /n/, following context [w], moderate-severe disorder group, male sex, the variant no repair strategy prevailed, and the phoneme was acquired with 7:6; for the phoneme /g/, the correct production was supported by the male sex, post-post-tonic and pre-pre-tonic syllables, preceding context with /u/, following context with /i/, moderate-severe and mild disorder group, no repair strategy prevailed, and the phoneme was acquired with 8:0. Conclusion: The subjects of this study showed more difficulty to acquire voiced segments, because no phoneme was acquired until the verified age. The acquisition of voiceless plosives did not occur in a linear way, frequent declines happened in different age groups. The children seem to use more simple motor acts to emit one segment after the other, to facilitate correct production. This class of consonants seems to be produced easily by subjects with phonological disorder, because the variant no repair strategy prevailed. Besides, these phonemes seem to be facilitated in no stressed syllables.